Learning styles of orang asli students / Intan Farahana Kamsin … [et al.] - Kamsin, Intan Farahana; Din, Rosseni; Mat Salleh, Nor Syazwani; Hamdan, Analisa; Manaf, Siti Zuraida (UiTM Press, 2016)
Learning style is an important aspect that should be taken into account while designing teaching and learning modules. The implementation of learning modules that addresses students’ learning styles can help them to achieve meaningful learning. This study aims to explore the learning styles of indigenous (known as Orang Asli in the Malay language, and henceforth) students. The respondents of this study are Orang Asli students from a southern region in Malaysia who were involved in an ICT Literacy Program. Data was generated through observations and interviews which were conducted during and after the implementation of the ICT Literacy program. Data analysis was performed using ATLAS.ti software. The findings showed the emergence of seven learning styles of Orang Asli students. The learning styles preferred by the Orang Asli learners are (i) group, (ii) individual, (iii) movement, (iv) hold and touch, (v) visual, (vi) auditory, and (vii) phrase level. This paper provides a detailed discussion of learning styles among Orang Asli students and thus, provides implications for the future developmental processes of online teaching and learning modules particularly for this particular group of students towards achieving meaningful learning.